Islamic mobility: Car culture in modern Malaysia. (July 2016) - Fischer, Johan
In a modern and respectable middle-class suburb outside Kuala Lumpur, the overtness of cars evokes intense speculation about the nature of the make-up of covert middle-class homes and the formation of Malay Muslim identities more generally. I argue that the more 'Islamic' cultures of consumption assert themselves in modern Malaysia, the more the growing Malay Muslim middle class is split between desiring cars as positional commodities, on the one hand, and claims for piety through consumption, on the other. An important question is how Malay Muslim middle-class identity is practised through divergent forms of car consumption. Discussing ethnographic material from fieldwork among Malay middle-class families, I show how car consumption generates not only distinctions, practices and moral symbolic boundaries but also ideas about Islam, nation and excess.